Pola Pemukimamn Kumuh Pada Pinggiran Bantara Rel Kereta Api Di Jl. Ampera Raya, Kec. Medan Timur, Kota Medan - Zega, Edwin Pasti Tabah; Saraswaty, Rina (Universitas Medan Area, 2025)
This study examines settlement patterns are places where humans live and carry out daily activities. The form of population distribution can be seen based on natural conditions and populations activities. According to wicaksosno (2010), a slum settlement pattern is a settlement where it is no longer possible to achieve a decent life for its residents. Jalan ampera raya, medan city, is one of the slum areas in the city of medan. This area is an area near the railroad tracks. The aim of the research is to look at the pattern of slum settlements on the outskirts of the railroad tracks. The research method was carried out using descriptive quantitative qualitative methods using field observations, interviews and questionnaires. According to the research results, the pattern of slum settlements in the area tends to be linear, following railway lines, and has the characteristics of denses buildings around centers of economic and educational activity. The level of security, ability to access public facilities, and waste management are some of the aspects affected by this condition. All these aspects attract the attention of local residents.